2015
DOI: 10.1111/febs.13283
|View full text |Cite
|
Sign up to set email alerts
|

The three‐dimensional structure of VIM‐31 – a metallo‐β‐lactamase from Enterobacter cloacae in its native and oxidized form

Abstract: The metallo-b-lactamase VIM-31 differs from VIM-2 by only two Tyr224-His and His252Arg substitutions. Located close to the active site, the Tyr224His substitution is also present in VIM-1, VIM-4, VIM-7 and VIM-12. The VIM-31 variant was reported in 2012 from Enterobacter cloacae and kinetically characterized. It exhibits globally lower catalytic efficiencies than VIM-2. In the present study, we report the three-dimensional structures of VIM-31 in its native (reduced) and oxidized forms. The so-called 'flapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…A). In contrast, in structures of enzymes such as VIM‐4, VIM‐7 and VIM‐31, His224 Nδ1 instead is H bonded to Nω1 of Arg228, apparently causing rotation of the His224 side chain to lie perpendicular to its position in VIM‐1 . In VIM‐1, the orientation of the His224 side chain more closely resembles that of the phenolic ring of Tyr224 in VIM‐2 (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A). In contrast, in structures of enzymes such as VIM‐4, VIM‐7 and VIM‐31, His224 Nδ1 instead is H bonded to Nω1 of Arg228, apparently causing rotation of the His224 side chain to lie perpendicular to its position in VIM‐1 . In VIM‐1, the orientation of the His224 side chain more closely resembles that of the phenolic ring of Tyr224 in VIM‐2 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Two extended loops, termed L3 (residues 60–66) and L10 (residues 221–241) border the active site. Superposition of the VIM‐1 structure with those of other VIM family members using pdbefold yields RMSD values for Cα‐atoms of between 0.28 Å (VIM‐26, pdb http://www.rcsb.org/pdb/search/structidSearch.do?structureId=4UWP ) and 0.83 Å (VIM‐31 (oxidized) pdb http://www.rcsb.org/pdb/search/structidSearch.do?structureId=4FSB ) Å, demonstrating that only small differences are evident between the overall fold of VIM‐1 and other structurally characterized VIM variants (Fig. B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inductively coupled plasma-atomic emission spectroscopy (ICP-AES) revealed that VIM-2 and VIM-20 bind 2.6 Ϯ 0.1 and 2.8 Ϯ 0.1 molar equivalents of Zn(II), respectively. Metal analyses indicate that VIM-2 and VIM-20 have a third Zn(II) binding site in addition to the two Zn(II) ions at the active site (21). To confirm the metal content, electrospray mass spectrometry (ESI-MS) was used to probe metal binding.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the arginine-containing peptides were found to be moderate to poor inhibitors of IMP-1, it is tempting to suggest that these lysine residues might be responsible for diminishing the affinity of cationic peptides for IMP-1. In addition, an analysis of the crystal structures of other members of the VIM family (including VIM-4 [66], VIM-7 [67], VIM-26 [68] and VIM-31 [69]) revealed the presence of negatively charged amino acids and the absence of positively charged groups at the surfaces vicinal to the active sites. Furthermore, L1 is characterized by a strongly negatively charged surface originating from large clusters of Asp and Glu residues near the active site [70], whereas CcrA possesses a surface of overall negative electrostatic potential with only one solvent-exposed lysine residue (Lys184) near the active site [71].…”
Section: Accepted Manuscriptmentioning
confidence: 99%